Salud, sexualidad y derechos: una mirada ampliada (2014)
The following article aims at analyzing the concept of sexual and reproductive health in Argentine within a wider framework, considering it as a constitutive part of human rights. This objective is based on the theoretical and normative framework established in Argentine since the creation of the National Program of Sexual Health and Responsible Procreation and the National Law of Holistic Sexual Education.